LITERASI PENDIDIKAN TINGGI DI SMA DARUL HIKAM BANDUNG MELALUI GUEST TEACHING - Saefullah, Nurul Hikmayaty; Januarsyah, Gilang (Midang, 2026)
This community service activity aims to enhance high school students’ literacy about higher education through a guest teaching session introducing university life and foreign language studies. The activity was conducted at SMA Darul Hikam Bandung and involved senior high school students preparing to pursue higher education. The method employed was community education through interactive outreach combining lectures, discussions, and an introduction to basic French vocabulary as an illustration of language and cultural studies. The material covered topics such as student life at university, essential skills required for successful academic adaptation, types of university students, and an overview of Universitas Padjadjaran and the Faculty of Cultural Sciences. Students were also introduced to simple French vocabulary related to daily expressions and French culinary culture. The results indicate that students showed strong enthusiasm when learning basic French expressions and actively participated in discussions about university life. However, most students still expressed a strong preference for science-related fields such as medicine and engineering rather than humanities programs. This finding highlights a gap between students’ curiosity about foreign languages and their willingness to pursue related academic fields. The activity demonstrates the importance of broader outreach efforts to promote humanities education among high school students.